Les médecins discutent-ils des habitudes de vie avec leurs patients? - Sauvageau, Chantal (Can J Public Health, 2008)
OBJECTIVE: To document counselling practices of general practitioners concerning lifestyle habits in the Capitale-Nationale region (Quebec City and area), from the patient’s perspective. METHOD: A cross-sectional telephone survey was carried out in 2006 among 482 patients (18–74 years of age) recruited in 11 medical clinics employing 84 general practitioners. RESULTS: At the visit immediately following the recruitment, 37% of participants reported having discussed smoking with their physician, 10% fruit and vegetable consumption and 33% physical activity. The prevalence of counselling on lifestyle habits increased as a function of pre-existing pathology. Participants said they were favourable to receiving advice on their habits in a proportion that varied from 82% (walk-in clinics) to 99% (health check) and 85% of them would modify their lifestyle habits if the advice was given by a physician (only 76% among smokers, p<0.0001). DISCUSSION/CONCLUSION: Even if they play a key role in chronic disease prevention, lifestyle habits were discussed in only 10 to 37% of medical visits and especially with patients who already had chronic disease or associated risk factors. Patients were very receptive to receiving advice on their lifestyle habits, even in walk-in clinics. It is now imperative to support general practitioners in the promotion of healthy lifestyle habits with all patients.